Synthesis and characterization of bacterial cellulose sulfates using a SO3/pyridine complex in DMAc/LiCl - Qin, Ziyu; Ji, Li; Yin, Xueqiong; Zhu, Li; Lin, Qiang; Qin, Jinming (Carbohydrate polymers, 2014)
•SBCSs with DS 0.10–1.50 were prepared homogeneously with SO3/Py in DMAc/LiCl.•SBCSs were characterized with FTIR, NMR, EA, XRD, GPC, and TGA.•Bacterial cellulose expresses higher reactivity than microcrystal cellulose.•Cellulose sulfates with DS>0.31 were soluble in deionized water.•The present method is suitable for preparing SBCS with DS lower than 0.6. Various sodium bacterial cellulose sulfates (SBCS) were prepared via the homogeneous sulfation of bacterial cellulose (BC) with a SO3/pyridine (Py) complex in a dimethyl acetamide/lithium chloride solution. The SBCSs were characterized using Fourier transform infrared spectroscopy, X-ray diffraction (XRD), carbon nuclear magnetic resonance spectroscopy, gel permeation chromatography, elemental analyses, and thermal gravimetric analyses. A variety of conditions (including various amounts of SO3/Py, temperatures, and reaction times) were utilized to obtain SBCSs with DS values that ranged from 0.10 to 1.50. The XRD profiles indicated that the SBCSs had a cellulose II analog polymorphous structure. The differences between BC and microcrystalline cellulose (MC) were studied in their respective reactions. BC is more reactive than MC in both the sulfation and depolymerization processes. The order of reactivity for COH is C6>C2>C3 for both BC and MC. Cellulose sulfates with DS values >0.31 were soluble in deionized water.